The Hispano-Filipino Church of Anini-y, Antique (1879-1995) - Fallar, Jose Romeo Louis Z., Jr
This study deals with the history of the Hispano-Filipino church of Anini-y, antique. Emphasis will be to the years 1879 to 1898 (construction period). The Hispano-Filipino Catholic church in Anini-y is unique, being the sole Spanish-vintage church still intact in Antique and being the oldest in Antique. Built during the late decade of the Spanish period, the church of Anini-y has survived various natural and man-made catastrophes. This study may provide people interested in local cultural and religious history a ready and available material., The data gathering used in this study were: informal and in-depth interviews with key informants. The character of labor was a mixture of voluntary cooperation and pressure by virtue and polo y servicios. The funds used in the construction of the church was from the Agustinian Federation and a sizable amount from Fray Geronimo Vaquerin's family in Spain. Although the construction of the church was initiated by the said priest, and maintained chiefly by foreign priest, Filipino expertise was employed for the realization of the construction of the said church. The history of the Hispano-Filipino church of Anini-y, to a certain extent, microcosm of Anini-y history.